Self-identity discrepancy theory: Exploring returning South African Cuban-trained medical students sense of belonging - Donda, B. M.; Singaram, V.; Hift, R. (South African Journal of Higher Education, 2022)
Background: The Nelson Mandela-Fidel Castro Collaboration programme (NMFCMC) between South Africa and Cuba was established in 1996. South African students, undergo five years of medical training in Cuba and finish the final eighteen months of training in South Africa. These students experience academic difficulties on their return. Methods: All twelve NMFCMC students enrolled at the University of KwaZulu-Natal in 2015 participated in this study. Data were elicited using focus group interviews, narrative interviews, found photovoice and the Collage Life Story Elicitation Technique. Results: Challenges faced by participants resulted in identity discrepancy, which in turn promoted unfavourable attitudes, affect, psychological and physical behaviours towards participants’ belongingness. Conclusion: Returning NMFCMC students experienced difficulties in assimilation due to identity discrepancies and frustrated sense of belonging. Focusing on reinforcing positive aspects of identity, and interpersonal relationships through moderating the tendency of local teachers and students to emphasise the “otherness” of the NMFCMC student is crucial.